2013
DOI: 10.1590/s0100-69162013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Thermal comfort in reduced models of broilers' houses, under different types of roofing materials

Abstract: The research was developed to evaluate the use of different types of roofing materials regularly used in poultry houses. Measurements of thermal comfort were made through the use of techniques such as the Black Globe and Humidity Index (BGHI), the Thermal Heat Load (THL) and Enthalpy (H). Conducted in the State University of Goiás, during the months of April and May, 2011, the experiment was composed of five different treatments: AC - Asbestos cement tiles, BA -Bamboo tiles, BAP - Bamboo tiles painted in white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 10 publications
(8 reference statements)
1
12
1
2
Order By: Relevance
“…The use of alternative materials in construction has been widely studied with the aim of combining low cost with thermal effectiveness [15][16][17][18][19][20]. Among the roofing studied, we found that those made from vegetable fibers [4] and bamboo have excellent resistance and high durability [21], besides being raw material found in large quantities and with low cost.…”
Section: Resultsmentioning
confidence: 99%
“…The use of alternative materials in construction has been widely studied with the aim of combining low cost with thermal effectiveness [15][16][17][18][19][20]. Among the roofing studied, we found that those made from vegetable fibers [4] and bamboo have excellent resistance and high durability [21], besides being raw material found in large quantities and with low cost.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the thermal environment, which encompasses temperature, humidity, air speed and radiation, interferes directly with breeding performance, changing food consumption and welfare of animals (PONCIANO et al, 2011;PONCIANO et al, 2012;SANTOS et al, 2014). Accordingly, environment inside the aviary sheds must be controlled so that the birds can be reared within a thermal comfort zone, avoiding negative thermal effects on animal yield (ALMEIDA & PASSINI, 2013;CORDEIRO et al, 2010;ROCHA et al, 2010;CAMPOS et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One of the main materials currently used in green buildings is the biocomposite: a combination of natural fibers (such as wood fibers, coir, hemp, jute, sisal, and flax) with polymer (RAMIRES et al, 2010), bitumen (ALMEIDA & PASSINI, 2013) or cement-based matrices (FARIAS FILHO et al, 2010). Natural fibers are biodegradable, renewable and widely available in Brazil.…”
Section: Introductionmentioning
confidence: 99%